Gender and preferences in a random sample - A combined experiment and survey study focusing on gender and economic preferences, interview by phone - Muren, Astri (University1, 2021)
The data is from an experimental study of a simple random sample of about 1000 adults from the Swedish population. The sample is similar by gender, age, income and education to this population. In addition, we have a high response rate, and can detect no differences between non-response and response groups by the comparison variables we have access to. In all relevant respects, we have a representative sample of the Swedish population, and one of the larger samples in the experimental economics literature.
The experimental data measures preferences in a broad range of standard incentivized decisions related to altruism, fairness, cooperation, trust, coordination, risk and competitiveness. Different treatments vary the salience of the participant’s own gender, as well as the gender of the counterpart. While gender differences in previous experimental studies typically are studied without controlling for sociodemographic characteristics, we have data on age, gender income and education and other sociodemographic variables.

Purpose:

The purpose of this study is to explore gender differences in a wide range of economic preferences in a representative sample. We will use a battery of standard games typically used in experimental economics and psychology, as well as common measures of risk preferences, competitiveness and time preferences. We will explore the same games and measures in three contexts, i.e with three settings, designed to explore different aspects of potential gender differences. These three settings will be investigated using three different treatments for each game and measure.

The survey is an OSU of the Swedish population aged 18-73 years from 2011-08-19. It has been implemented by two methods, telephone interviews and distribution of printed questionnaires.
Of the sample, 2349 respondents answered by telephone.

Data är från en experimentell studie av ett obundet slumpmässigt urval av cirka 1000 vuxna från den svenska befolkningen. Urvalet överensstämmer med populationen efter kön, ålder, inkomst och utbildning. Svarsfrekvensen är hög och vi finner inga skillnader mellan bortfallsgrupper och svarsgrupper för de jämförelsevariabler vi har tillgång till. I alla relevanta avseenden har vi ett representativt urval av den svenska befolkningen, och ett av de större urvalen i den vetenskapliga litteraturen inom experimentell ekonomi.
De experimentella data mäter preferenser i ett brett spektrum av standardbeslut som rör altruism, rättvisa, samarbete, förtroende, samordning, risk och konkurrensvillighet. Olika behandlingar varierar deltagarens genderidentitet, liksom motpartens kön. I tidigare experimentella studier studeras könsskillnader ofta utan att kontrollera för sociodemografiska egenskaper; här finns uppgifter om ålder, kön, inkomst och utbildning och andra sociodemografiska variabler.

Syfte:

Vi vill studera könsskillnader i preferenser i ett representativt urval, med tre olika experimentstrukturer. De flesta experimentella studier görs med universitetsstudenter som deltagare. Projektets syfte är att närmare undersöka i vilken utsträckning resultaten från experimentella studier med universitetsstudenter även föreligger i ett urval som är representativt för befolkningen som helhet. Detta har inte tidigare studerats.

Undersökningen är ett OSU av Sveriges befolkning i åldrarna 18-73 år från 2011-08-19. Den har genomförts med två metoder, telefonintervjuer och utskick av tryckta enkäter.

Storleken på urvalet var 2349 till telefonintervjun. Innan intervjuprocessen påbörjades genomfördes ett utskick till samtliga i urvalet för telefondelen med en beskrivning av undersökningen.
Kön och preferenser i ett slumpmässigt urval - Kombinerat experiment och surveyundersökning med fokus på kön och ekonomiska preferenser, telefonintervju
Keywords: economics; ekonomi; trust; förtroende; risk; risk; income; inkomst; gender; genus; gender role; könsroll; cooperation; samarbete; Cooperative Behavior; Samarbete; Dangerous Behavior; Riskbeteende; Risk Assessment; Riskbedömning; justice; rättvisa; experimental economics; experimentell ekonomi; competitiveness; konkurrensvillighet; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); ECONOMICS; EKONOMI; Social Sciences; Samhällsvetenskap